2016
DOI: 10.1111/joor.12430
|View full text |Cite
|
Sign up to set email alerts
|

Multidirectional lip‐closing force in adult females after short‐term lip training

Abstract: The purpose of this study was to investigate the multidirectional lip-closing force in adult females before and after short-term lip training. Sixty-six Japanese females participated in this study. The subjects performed lip training that involved maintaining 200 or 400 g of bottled water in the oral vestibule. The signals of directional lip-closing force were investigated in eight directions before training and 5 and 7 days after the lip training. The differences in the closing force between pre- and post-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…The effects of the application of low (200 grams) and high loads (400 grams) using bottled water attached by a string to an intra-oral plate in the oral vestibule were compared. Both training groups showed an increase in lip-closing force when compared to the control group, and the change did not differ between the two training groups [23]. These results would suggest that a very short-term program (two times a day for approximately one week) may increase the lip-closing force.…”
Section: Influence Of Age On Lip Training Responses In Healthy Adultsmentioning
confidence: 67%
See 3 more Smart Citations
“…The effects of the application of low (200 grams) and high loads (400 grams) using bottled water attached by a string to an intra-oral plate in the oral vestibule were compared. Both training groups showed an increase in lip-closing force when compared to the control group, and the change did not differ between the two training groups [23]. These results would suggest that a very short-term program (two times a day for approximately one week) may increase the lip-closing force.…”
Section: Influence Of Age On Lip Training Responses In Healthy Adultsmentioning
confidence: 67%
“…Of the previous studies included, three studies included both men and women pooled together [7,9,22], and two studies [12,23] included only women ( Table 1). Four of the five studies included control groups to better indicate if there was a difference in lip strength with training [7,9,22,23], while the other defined a change as anything that exceeded the baseline value. A Lip trainer was used for training in three studies (Table 3).…”
Section: Influence Of Sex On Lip Training Responses In Healthy Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data agreed with other studies that investigated the positive effects of lip training in healthy adults. Fujiwara et al [32] found that daily strength training of lip closing may be effective in increasing lip function. Arakawa et al [33] and Kaede et al [34] concluded that labial closure strength significantly increased after 2 and up to 4 weeks’ training.…”
Section: Discussionmentioning
confidence: 99%